The pibid and the management of the school: “Implementation gap”? - Cavalcanti, Paula Arcoverde (Seven Editora, 2023)
This work aims to understand how the management of the public institution of Elementary School II could contribute to the occurrence of the "implementation gap" in the PIBID-GEO subproject in the period from 2016 to 2018. Based on Public Policy Analysis and the Policy Cycle as a virtually constructed analytical tool, the debate revolves around the moment of implementation as an uninterrupted process that may suffer some kind of problem caused by the street-level bureaucrats. This is a qualitative research developed through direct end unsystematic observation during the period in which the activities of the subproject were developed and, it was observed, that the maneuvers performed by managers due to their discretion did not collaborate with the implementation process, making it difficult for PIBID-GEO to be effectively "materialized" at the level of the educational institution. DOI:https://doi.org/10.56238/sevened2023.006-042